O cuidar/educar nas narrativas de professoras de uma creche de Rio Branco/AC - Silva, Menilce Antonia da (2014)
This research aims to know and understand the concepts and practices narrated on the care / education by the teachers of Rio Branco / AC crèche de and brings the central question: What concepts and practices on the care / education are narrated by the teachers? The qualitative research approach is anchored in studies Biklem and Bogdan (1994), with the option, the case study, based on André (1986, 2005). Data collection occurred through semi-structured interviews and observations of moments of the practice of the four surveyed teachers. The theoretical framework brings in conceptions of childhood: Kulhman (2012), Aries (2006), Farias (2005); Conceptions of child development: Oliveira (1992.1999); Vigotsky (2001) and Leontiev (2001); Care / education: Kramer (2005), Didonet (2011); Boff (1999), Azevedo (2013); Joke and Interactions: Corsino (2009), Borba (2009), Moura (2009), Oliveira (2011), Moyles (2002), Rabbit and Pedrosa (1995), Cruz and Santos (2006); Sarmento (2002, 2003, 2005 , 2009), which also deals with conceptions of childhood and interactions; Professional Identity: Dubar (1997), Ciampa (1994) and Teacher Training, Garcia (1999), Nóvoa (1992, 1995, 1999), Oliveira (2001), Kramer (2005), Willow (2009) and Gomes (2009) .Das interviews and observations revealed three axes of analysis dealing with the following points: personal and professional life of teachers and the establishment of the identity of the same; Conceptions about childhood care / education and on the play and interactions. The results show the following evidence: the identity of teachers is becoming an every day, the intersection of the personal and professional dimensions, due to their lived experiences and continuing education. About play and interactions became explicit in the narrative that teachers conceive them as important elements in the development of children of nursery and this fact is evident when they speak with an emphasis on these two aspects, revealing that seek to prioritize these actions in pedagogical practices. With regard to the care / education, the narratives suggest that when teachers started teaching in the nursery, only brought expertise on working with children from 2:03 years, too, brought only their personal experiences of caring through of experiences with children or with other children of the contexts from which they were inserted. Because they are in a continuous process of professional development, the concepts and practices on the care / education, are also constituting themselves. About this constitution, we can infer that in some lines, they understand it is a unique aspect of their teaching actions in the nursery, which points to a conception of binomial. However, some lines refer to an understanding that reflects, at certain times, disregard the aspect of care as teaching, which reveals a dichotomous conception between care and education. So narratives have some conflict in relation to the concepts and practices, however, this conflict is justified when we consider that the social function of the nursery has a whole historical constitution. Also, the little time that daycare centers are linked to education, is expressed in the concepts and practices narrated by teachers. Accordingly, we find that even in the face of conflicts of professionals, their data show progress in bringing concepts, showing different from those that supported the service that small children were, where they were present, basically, the welfare and philanthropic aspects and institutions were seen as a place of custody and their professional caregivers.